Investigation of the Influence of Liquid Motion in a Flow-based System on an Enzyme Aggregation State with an Atomic Force Microscopy Sensor: The Effect of Water Flow - Yuri D. Ivanov; Tatyana O. Pleshakova; Ivan D. Shumov; Andrey F. Kozlov; Tatyana S. Romanova; Anastasia A. Valueva; Vadim Yu. Tatur; Igor N. Stepanov; Vadim S. Ziborov (Applied Sciences, 2020)
The influence of liquid motion in flow-based systems on the aggregation state of an enzyme and on its enzymatic activity was studied, with horseradish peroxidase (HRP) as an example. Our experiments were carried out in a setup modeling the flow section of the biosensor communication with a measuring cell containing a protein solution. Studies were conducted for a biosensor measuring cell located along the axis of a spiral-moving liquid flow. The aggregation state of the protein was determined with an atomic force microscopy-based sensor (AFM sensor). It has been demonstrated that upon flowing of water through silicone biosensor communications, an increased aggregation of HRP protein was observed, but, at the same time, its enzymatic activity did not change. Our results obtained herein are useful in the development of models describing the influence of liquid flow in biosensor communications on the properties of enzymes and other proteins. This is particularly important for the development of serologic protein biosensors, which are beginning to be used for the early diagnosis of oncological diseases (such as brain cancer, prostate cancer, breast cancer etc.). The results obtained herein should also be taken into account when considering possible changes in hemodynamics due to increased protein aggregation.